Investigating Conflict Management Styles and Emotional Intelligence of Unit Charge Nurses - Meltem Özduyan Kılıç; Sergül Duygulu (Galenos Publishing House, 2024)
Objective: This study investigated the relationship between conflict management styles and emotional intelligence of unit charge nurses. Method: This descriptive, cross-section, and correlational study was conducted between December 2016 and April 2017 with 197 unit-charge nurses. Data were collected using a demographic data sheet, the Rahim Organizational Conflic Inventory, and the Modified Schutte Emotional Intelligence Scale. Data were analyzed using power analysis, descriptive statistics, pearson correlation analysis, and multiple regression analysis. Results: Of all unit charge nurses, 61.4% experienced conflict with staff nurses. When conflict occurs, they tend to use the integrating style (4.17±0.37) mostly. The unit charge nurses' emotional intelligence total mean scores were 88.46±7.74 (min: 22, max: 110). The results showed a positive, significant, and moderate correlation between total emotinal intelligence scores and integration style (r=0.432; p<0.01). Emotional intelligence explains approximately 23% of the total variance in the integrating style (∆R2=0.226). Conclusion: The study results showed that unit charge nurses' emotional intelligence abilities can help them effectively manage conflicts with staff nurses. Therefore, healthcare organizations should focus on training programs on conflict management and emotional intelligence to improve effective conflict management.